A study on tools of total quality management towards decision making in organization / Habibah Nik Mat - Nik Mat, Habibah (Faculty of Business and Management, 2012)
The research studies on tools of total quality management which is benchmarking and quality control circle in improving decision making in organization. There are two objective of study that researcher want to achieve. Firstly, to determine relationship between benchmarking with improvement decision making in organization. Secondly, to determine relationship between quality control circle with improvement decision making in organization. The research was conducted among employee of Puspakom Sdn Bhd and involving 50 respondents as the sample size of research. All respondent need to answer the questionnaires related to topic of research. The result was obtained through data that has been analyzed using reliability test, frequency analysis and regression analysis. The conclusion for this study was based on outcome of data analysis in chapter 4. At the end of study, the researcher makes some recommendation for organization and further researcher.